Aspirin for Venous Ulcers: Randomised Trial (AVURT): study protocol for a randomised controlled trial. Issue 1 (December 2015) - Tilbrook, Helen; Forsythe, Rachael; Rolfe, Debbie; Clark, Laura; Bland, Martin; Buckley, Hannah; Chetter, Ian; Cook, Liz; Dumville, Jo; Gabe, Rhian; Harding, Keith; Layton, Alison; et al.
Abstract Background Venous leg ulcers (VLUs) are the commonest cause of leg ulceration, affecting 1 in 100 adults. There is a significant health burden associated with VLUs – it is estimated that the cost of treatment for 1 ulcer is up to £1300 per year in the NHS. The mainstay of treatment is with graduated compression bandaging; however, treatment is often prolonged and up to one quarter of venous leg ulcers do not heal despite standard care. Two previous trials have suggested that low-dose aspirin, as an adjunct to standard care, may hasten healing, but these trials were small and of poor quality. Aspirin is an inexpensive, widely used medication but its safety and efficacy in the treatment of VLUs remains to be established. Methods/Design AVURT is a phase II randomised double blind, parallel-group, placebo-controlled efficacy trial. The primary objective is to examine whether aspirin, in addition to standard care, is effective in patients with chronic VLUs (i.e. over 6 weeks in duration or a history of VLU). Secondary objectives include feasibility and safety of aspirin in this population. A target of 100 participants, identified from community leg ulcer clinics and hospital clinics, will be randomised to receive either 300 mg of aspirin once daily or placebo. All participants will receive standard care with compression therapy. The primary outcome will be time to healing of the reference ulcer. Follow-up will occur for a maximum of 27 weeks. The primary analysis will use a Cox proportional hazards model to compare time to healing using the principles of intention-to-treat. Secondary outcomes will include ulcer size, pain evaluation, compliance and adverse events. Discussion The AVURT trial will investigate the efficacy and safety of aspirin as a treatment for VLU and will inform on the feasibility of proceeding to a larger phase III study. This study will address the paucity of information currently available regarding aspirin therapy to treat VLU. Trial registration The study is registered on a public database with clinicaltrials.gov (NCT02333123 ; registered on 5 November 2014).